TURNKEY PROJECT DAN DINAMIKA PENGATURAN KETENAGAKERJAAN ASING DI INDONESIA - Muhammad Badaruddin; Suciliani Octavia (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2017)
China’s aggressiveness to conduct its belt and road initiatives through the Pacific Rim meets Presiden Joko Widodo’s ambition to attract foreign investment. The Indonesian President has been very ambitious in reaching high economic growth that requires readiness of infrastructure support. In dealing with China, Indonesia is required to accept China’s turnkey project scheme for infrastructure development, particularly in welcoming Chinese workers and equipments as an integral part of the project package. As a consequence, Indonesia has to loose its foreign worker regulation despite creating new contradictions with its domestic policy. This article is trying to investigate China’s funding and investment influence in Indonesia particularly in the foreign worker management during the period of President Joko Widodo Administration. The research conducted with qualitative method particularly the case study to analyze a sequential case in the field. Result of this research shows that the China’s turnkey project scheme impacts the foreign worker management in Indonesia. Our data displays pretty massive cases related to Chinese workers, extending from the violation of immigration regulation to the increase number of smuggling and other criminal activities. This research also highlight the indication that the Joko Widodo Administration tend to loose the Indonesian foreign worker regulations, as well as being less assertive in processing varous immigration cases which related to Chinese foreign workers. Moreover, the Jokowi administration has changed lots of regulations despite it has conflicting issues with the Law on Foreign Worker. On the other hand, the Parliament’s Special Committee on the Foreign Worker Issue has recommended the Jokowi Administration to pay more serious attention on cases related to the Chinese workers. Keywords: Turnkey Project, Foreign Investment, Foreign Aid, Regulation on Foreign Worker, Illegal Foreign Worker Abstrak Agresivitas Pemerintah China dalam menjalankan belt and road initiatives ke berbagai negara yang terpetakan dalam road map-nya, bertemu dengan kepentingan Indonesia di bawah Pemerintahan Joko Widodo. Yakni ambisi untuk mengejar target pertumbuhan yang tinggi yang mempersyaratkan dibangunnya berbagai proyek infrastruktur sebagai penunjangnya. Pembangunan berbagai proyek tersebut membutuhkan ketersediaan anggaran yang cukup besar dalam waktu cepat. Salah satu strategi pemenuhannya adalah dengan mencari investasi maupun pinjaman luar negeri, terutama asal China yang secara koinsiden juga sedang agresif berekspansi. Kehadiran investasi dan pinjaman asal China di Indonesia dengan skema turnkey project ternyata menimbulkan ekses yang tidak sederhana. Skema tersebut menjadi salah satu pintu masuk tenaga kerja asal China melalui proyek-proyek infrastruktur yang ternyata menimbulkan permasalahan baru dalam pengaturan sektor ketenagakerjaan asing (TKA) di Indonesia. Irisan fenomena dari keinginan untuk merealisasikan proyek infrastruktur secara cepat, kebutuhan anggaran yang cukup tinggi terhadap pendanaan proyek dari China, dan kekurangsiapan dalam pengaturan masuknya tenaga kerja asing adalah fokus dari penelitian yang hasilnya penulis tuangkan dalam artikel ini. Dari penelitian yang dilakukan, terdapat peningkatan berbagai kasus yang terkait dengan kehadiran TKA asal China, antara lain adalah penyalahgunaan visa, penyalahgunaan status kerja, sampai pada meningkatnya angka penyelundupan dan tindak kriminalitas. Penelitian ini menggunakan metode kualitatif dengan menganalisis secara triangular beberapa data yang didapatkan melalui wawancara terhadap narasumber primer, pengolahan dokumen-dokumen resmi, analisis terhadap berbagai literatur dan pemberitaan media massa. Kata Kunci: Turnkey Project, Investasi Asing, Pinjaman Asing, Tenaga Kerja Asing, Peraturan Ketenagakerjaan